2021
DOI: 10.1080/15213269.2021.1959350
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Distraction: An Experience Sampling Study among Adolescents

Abstract: A widespread concern in society is that adolescents experience an increased inability to concentrate and sustain attention because they are continuously distracted by social media. The current experience sampling method (ESM) study examined whether adolescents who use more social media than their peers experience more distraction (between-person association), whether social media use (SMU) and distraction cofluctuate within adolescents (momentary within-person associations), and to what extent this within-pers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 76 publications
3
36
2
Order By: Relevance
“…The current study showed that social media-related distraction is indeed common among adolescents, with 77% of adolescents experiencing more distraction as they spend more time using social media. We partly replicated a recent ESM study by Siebers et al (2021), which was conducted in November 2019 among the same sample of adolescents, six months before the current study. In comparison to Siebers et al (2021), we found both a higher positive between-person association (β = .48 vs β = .31 in Siebers et al) and a higher within-person association of SMU with (β = .18 vs β = .12 in Siebers et al).…”
Section: Investigating Hypothesesmentioning
confidence: 76%
See 4 more Smart Citations
“…The current study showed that social media-related distraction is indeed common among adolescents, with 77% of adolescents experiencing more distraction as they spend more time using social media. We partly replicated a recent ESM study by Siebers et al (2021), which was conducted in November 2019 among the same sample of adolescents, six months before the current study. In comparison to Siebers et al (2021), we found both a higher positive between-person association (β = .48 vs β = .31 in Siebers et al) and a higher within-person association of SMU with (β = .18 vs β = .12 in Siebers et al).…”
Section: Investigating Hypothesesmentioning
confidence: 76%
“…The current study extends the study of Siebers et al (2021) by examining factors that may explain why adolescents differ in their tendency to become distracted by SMU. Scholars have suggested that a healthy usage of social media is obtained when social connectivity and disconnectivity are properly in balance (Vanden Abeele, 2020).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations